Analisis Kebugaran Jasmani Siswa Melalui Tes Lari 1000 Meter Siswa Kelas 5 SDN Pojok 2 Kota Kediri - Dewi Yuliana; Mohammad Nur Kholis; Ahmad Zakiyyunnuhaa (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the physical fitness level of fifth-grade students at SDN Pojok 2 Kota Kediri through a 1000-meter running test. A descriptive quantitative approach was used with a total sample of 30 students, consisting of 17 boys and 13 girls. The results showed that most students fell into the